Climate is More Than Just Weather: Gap of Knowledge about Climate Change and Its Psychological Impacts among Indonesian Youth - Siti Jaro'ah; Vania Ardelia; Nurchayati; Miftakhul Jannah (CV. Literasi Indonesia, 2023)
Climate change is an environmental threat in Indonesia, affecting not only physical and environmental but also psychological conditions. Youth are among the most vulnerable groups in society to the impacts of climate change. However, the attention and involvement of young people on climate change issues are minimal. This study aimed to determine the knowledge and sources of information about climate change, and the impacts of climate change on young people aged 15-29 years. A descriptive qualitative approach with open-ended questionnaires was used for the study with 107 participants. Findings revealed that young people equated climate change with changes in weather or seasons, and also the rising temperatures. Indonesia's climate is increasingly extreme, erratic, and hotter, leading to physical, psychological, and social impacts. Participants felt worried, scared, anxious, sad, angry, panicked, and confused as the psychological impacts of climate change. Surprisingly, instead of experiencing negative emotions, some participants felt nothing and expressed curiosity about climate change. The internet and social media are the main sources of information. Meanwhile, friends are the first option to talk about climate change. Results indicate that Indonesian youth have little understanding of climate change, but they are aware of the crisis. Further research on the psychological impacts of climate change is needed.